2018
DOI: 10.3390/genes9030163
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Phylogeography of Rhizobial Symbionts Nodulating Legumes of the Tribe Genisteae

Abstract: The legume tribe Genisteae comprises 618, predominantly temperate species, showing an amphi-Atlantic distribution that was caused by several long-distance dispersal events. Seven out of the 16 authenticated rhizobial genera can nodulate particular Genisteae species. Bradyrhizobium predominates among rhizobia nodulating Genisteae legumes. Bradyrhizobium strains that infect Genisteae species belong to both the Bradyrhizobium japonicum and Bradyrhizobium elkanii superclades. In symbiotic gene phylogenies, Geniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 168 publications
6
41
2
Order By: Relevance
“…None of our isolates was affiliated to Bradyrhizobium, unlike in previous studies on C. spinosa in the northeast of Algeria [6] and C. spinosa and C. infesta in different areas of Sicily [5]. Several authors have demonstrated that Bradyrhizobium predominates among rhizobia nodulating Genisteae [47][48][49][50]. However, in some other studies, Genistoid plants, such as Genista saharae, Retama raetam or Retama sphaerocarpa, were nodulated by Sinorhizobium (formerly Ensifer), Rhizobium, Mesorhizobium and Phyllobacterium [39,51,52].…”
Section: Rhizobia Isolated From C Villosa Nodules In Tunisian Arid Scontrasting
confidence: 79%
“…None of our isolates was affiliated to Bradyrhizobium, unlike in previous studies on C. spinosa in the northeast of Algeria [6] and C. spinosa and C. infesta in different areas of Sicily [5]. Several authors have demonstrated that Bradyrhizobium predominates among rhizobia nodulating Genisteae [47][48][49][50]. However, in some other studies, Genistoid plants, such as Genista saharae, Retama raetam or Retama sphaerocarpa, were nodulated by Sinorhizobium (formerly Ensifer), Rhizobium, Mesorhizobium and Phyllobacterium [39,51,52].…”
Section: Rhizobia Isolated From C Villosa Nodules In Tunisian Arid Scontrasting
confidence: 79%
“…Although European, African and American species of Lupinus are generally considered to be nodulated by slow‐growing rhizobia affiliated to different Bradyrhizobium lineages (see Andrews and Andrews ; Stępkowski et al . for reviews), other reports have shown that the fast‐growing rhizobial species Phyllobacterium (Valverde et al . ), Ochrobactrum (Trujillo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lupinus species have been shown to be nodulated by slow-growing rhizobia of the genus Bradyrhizobium, including B. japonicum, B. lupini, B. canariense, B. diazoefficiens and B. elkanii species (Peix et al 2015;Shamseldin et al 2017;Vel azquez et al 2017;Ste z pkowski et al 2018;Mellal et al 2019). Also, fast-growing strains of the species Ochrobactrum lupini isolated from Lotus honoratus (Trujillo et al 2005), of the genus Microvirga from L. texensis (Ardley et al 2012), L. micranthus (Msaddak et al 2017a(Msaddak et al , 2017b and L. subcarnosus (Beligala et al 2017) and Burkholderia have been isolated from the later plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic diversity and community structure of rhizobia, which are natural microsymbionts of legumes, are commonly studied using a given leguminous plant as a trap plant, following the isolation of bacteria from nodules and their further characterization (genetic, functional, and phenotypic characterization). Such studies suggest that selective enrichment of rhizobial strains from the pool of the rhizobial community in the soil occurs based on symbiotic compatibility (gene background) with the plant, and depending on the plant used, the biodiversity of isolates can be restricted [78,79].…”
Section: In Vitro Assays In Vivo Assays: Tomatomentioning
confidence: 99%